Pengaruh Penggunaan Media Elektronika Terhadap Motivasi Belajar Pendidikan Agama Kristen Siswa Kelas IX Di SMP Negeri 1 Sipoholon Tahun Pembelajaran 2023/2024 - Ruben Sitinjak (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2023)
The research aims to determine the effect of using electronic media on the learning motivation of PAK class IX students at SMP Negeri 1 Sipoholon for the 2023/2024 academic year. The research hypothesis is that there is a positive and significant influence between the use of electronic media on the learning motivation of PAK class IX students at SMP Negeri 1 Sipoholon for the 2023/2024 academic year. This research is a regression research using the Quantitative Inferential Method.The population of all class IX students at SMP Negeri 1 Sipoholon for the 2023/2024 academic year is 190 people. Random sampling (random sampling) was 30% of the total population, namely 57 people. The research instrument is a closed questionnaire.The results of the analysis requirements obtained a value of rxy=0.678>rtabel=0.226 and tcount=6.840>ttable=2.000 indicating a relationship between the use of electronic media and students' PAK learning motivation and obtained a regression equation . Hypothesis testing obtained Fcount=46.542>Ftable=1.39 so H0 is rejected and Ha is accepted. The research concluded that there was a positive and significant influence between the use of electronic media on the learning motivation of PAK class IX students at SMP Negeri 1 Sipoholon for the 2023/2024 academic year, amounting to 45.97%.